Estudo sobre a adoção de metodologias ativas para o enfrentamento da evasão no curso de licenciatura em física da UNIPAMPA - Franco, Bianca Vasconcelos do Evangelho (2019)
In the present dissertation, through a qualitative design of a case study using the grounded theory and based on the longitudinal model of Vincent Tinto, we propose the use of active methodologies, aiming at minimize the high dropout rates in the Physics Degree course at Unipampa Campus Bagé. Thus, through participant observations, questionnaires, and interviews, we investigated the potential of active methodologies to contribute to increased self-efficacy beliefs, a sense of belonging, and curriculum perceptions. Unlike most studies found in the literature, which predominantly seek to identify the reasons and factors for dropout, in this research we use active methodologies to investigate the students' constructs in the curriculum component of General Physics I. Thus, actions to combat dropout in the Unipampa Physics Degree freshmen began since the first day of the first semester of 2019. At the end of the semester we observed that the use of innovative and active proposals and methodologies, in addition to making Significant content, improving students' perception of curriculum, also contributed (in most cases) to increasing their self-efficacy beliefs (the belief in their potential to complete a degree), and their sense of belonging (feeling of being important and integrated agent in your course, that is, the student feel an important and integral part graduation and the group to which it belongs). In this context, we verified through data analysis, evidence of increase in students' constructs, from the application of active methodologies. We also identified the need for insertion of introductory physics curriculum components that foster the development of a teaching identity by the students in the course, as well as stimulate and encourage an increase of their constructs and that follow-up actions of the academic trajectory of the undergraduate occur since your admission until the end of your degree. Thus, institutional actions are implemented and evaluated permanently, so that in the long term dropout rates are strongly minimized.